2013
DOI: 10.1108/jes-05-2011-0066
|View full text |Cite
|
Sign up to set email alerts
|

Real estate market factors and foreign real estate investment

Abstract: Purpose -The purpose of this paper is to examine the effects of real estate market factors on foreign real estate investment (FREI). Design/methodology/approach -Applying panel data technique, this paper uses related observations from 31 countries (inclusive of developed countries and emerging market economies) between 2000 and 2008 to investigate the relationships between real estate market factors and FREI. Findings -Controlling for market size, infrastructure and political stability, the results for all cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 50 publications
0
11
0
2
Order By: Relevance
“…For China, He and Zhu (2010) showed that aside from satisfactory demographic conditions, already invested foreign capital attracts both foreign developers as well as more crossborder investors. In addition, Rodríguez andBustillo (2010), Gholipour Fereidouni andAriffin Masron (2013) and Farzanegan and Gholipour Fereidouni (2014) observed marketspecific property prices to be influential. Interestingly, Gholipour Fereidouni and Ariffin Masron (2013) found real estate market transparency to be an important determinant for foreign investors, but Farzanegan and Gholipour Fereidouni (2014) did not confirm this finding.…”
Section: Related Literature and Hypotheses Derivationmentioning
confidence: 98%
“…For China, He and Zhu (2010) showed that aside from satisfactory demographic conditions, already invested foreign capital attracts both foreign developers as well as more crossborder investors. In addition, Rodríguez andBustillo (2010), Gholipour Fereidouni andAriffin Masron (2013) and Farzanegan and Gholipour Fereidouni (2014) observed marketspecific property prices to be influential. Interestingly, Gholipour Fereidouni and Ariffin Masron (2013) found real estate market transparency to be an important determinant for foreign investors, but Farzanegan and Gholipour Fereidouni (2014) did not confirm this finding.…”
Section: Related Literature and Hypotheses Derivationmentioning
confidence: 98%
“…The difficulty in accessing development funds, underdeveloped mortgage market and high interest rates, land tenure arrangements, lengthy building permit/warrant approval and land acquisition and registration processes discourage real estate investments in Ghana [33]. Similarly, sound financial and economic structure, stability of the economy, restrictions and regulations on investors and legal regulation are the most important issues affecting the market attractiveness in Southeast Asian cities [41].…”
Section: Economic Factorsmentioning
confidence: 99%
“…The underlying cost of labor, land and materials in delivering the housing to the market is a concern. Lower financing costs and higher levels of transparency in real estate market attract greater amounts of real estate investment [41]. In addition, transaction and building material costs influence development in real estate [15], [20], [28].…”
Section: Finance and Related Costsmentioning
confidence: 99%
“…A number of processes have affected the real estate market in Australia. The literature on Australian cities has usually focused on foreign capital flows and individual investments at a macro level during the boom period [16,[18][19][20]. However for the foreign property investment 'bust' period, there has been little academic work undertaken.…”
Section: Empirical Research Gap Analysismentioning
confidence: 99%